2011
DOI: 10.1002/jcc.21737
|View full text |Cite
|
Sign up to set email alerts
|

Extensive theoretical study on electronically excited states and predissociation mechanisms of sulfur monoxide including spin–orbit coupling

Abstract: The potential energy curves of the 69 Ω states generated from the 24 Λ-S states of sulfur monoxide are calculated for the first time using the internally contracted multireference configuration interaction method with the Davidson correction and the entirely uncontracted aug-cc-pV5Z basis set. Spin-orbit coupling is taken into account by the state interaction approach with the full Breit-Pauli Hamiltonian. Very good agreement is achieved between our computed spectroscopic properties and the available experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…In this study, we show new ab initio potential energy curves. On the basis of the reported results of other studies, both numerical and experimental, , the spectroscopic constants from our study falls within the range of previously reported data. On the basis of the improved methodology of Danielache et al, we present high-resolution total absorption cross sections for the A 3 Π ← X 3 Σ – transition and two nonadiabatically coupled potential ([C 3 Π–C′ 3 Π] ← X 3 Σ – and [B 3 Σ – –3 3 Σ – ] ← X 3 Σ – ) transitions.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we show new ab initio potential energy curves. On the basis of the reported results of other studies, both numerical and experimental, , the spectroscopic constants from our study falls within the range of previously reported data. On the basis of the improved methodology of Danielache et al, we present high-resolution total absorption cross sections for the A 3 Π ← X 3 Σ – transition and two nonadiabatically coupled potential ([C 3 Π–C′ 3 Π] ← X 3 Σ – and [B 3 Σ – –3 3 Σ – ] ← X 3 Σ – ) transitions.…”
Section: Introductionsupporting
confidence: 92%
“…17 Elks and Western studied fluorescence, excitation lifetimes, and rotational constants on the A 3 Π state using multiphoton ionization techniques. 18 A computational work by Yu and Bian 19 analyzes the excited electronic state potentials and the spin−orbit coupling between them. The work by Borin and Ornellas analyzed the potential energy curves of low-lying singlet and triplet electronic states of SO 20 and A 3 Π ← X 3 Σ − transition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We start this discussion showing the spectroscopic parameters R e , D e , and w e of both SO(B 3 Σ − ) and ArS( 1 Σ + ) diatomic species. For comparison, also gathered in this same table are the results experimental and other theoretical [14,15]. All our results presented show good agreement with other works.…”
Section: Resultssupporting
confidence: 87%
“…Diode laser [ 15 , 16 ] and Fourier transform [17] vibration-rotation spectra are also available. The electronic structure of SO has also been investigated by means of ab initio calculations, e.g., [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%